An An essay on political polarization - Perić Diligenski, Tijana D. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In the paper, the author tries to answer the question, what are the sources of polarization in modern authoritarian states (that are procedurally democratic), and what are the key differences (points of conflict) between the polarized parties? Research attention is focused on the analysis of the political and broader social effects of polarization and on the dilemma of whether it is even possible to reduce the negative effects of the actions of value-opposing actors? The author observes a universal sociological regularity according to which the roots of polarization almost unmistakably arise from the pluralism of social identities that are built on ideology, religion, and ethnicity and which tend to be manipulated by political elites. Primarily, artificially created political polarization is a strategy for mobilizing the electoral base, and secondarily it represents a means for legitimizing and consolidating populist and authoritarian regimes. Once society starts to polarize, intra-group loyalty is strengthened within competing political and other groups and a group identity is created that is sensitive to any Otherness, which is reflected in conflicts with social groups and movements that are opposed in terms of interests and values.
Keywords: social cleavages, polarization, identity, democracy, politics